Autism spectrum disorder and its impact on child development: an integrative review - Melo, Hellen Pereira (2021)
Objective: The objective of this research is to analyze, in the scientific literature, the impact of Autistic Spectrum Disorder (ASD) on child development, to identify which aspects of child development are most affected by Autism and to analyze the learning process of the autistic child. Methodology: This is a bibliographic research developed using the Integrative Review method. Results: The results show that the most affected aspects in child development are the delay in Neuropsychomotor Development related to global motor skills, balance and language / temporal organization, changes that occur in a non-linear way and can have an impact on the learning process. Regarding the learning process of the autistic child, the literature points out that this process must be carried out through different pedagogical methodologies so that this child creates autonomy and progress in their learning. Conclusion: It is concluded that the daily and specialized monitoring of children with ASD reveals how much it is necessary for a support professional who is prepared, who seeks creative and playful alternatives that are adapted and individualized, thus facilitating the learning of children with ASD.